2021
DOI: 10.2174/2210315510999200607182700
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin Enriched Black Tea Extract Alleviates Diabetic Nephropathy by Suppressing Hyperglycaemia-Mediated Oxidative Stress and Inflammation in Streptozotocin-Induced Rats

Abstract: Background: Diabetic nephropathy (DN), a microvascular complication of diabetes has been a significant health issue globally. However, theaflavin enriched black tea extract (BTE-TF) could restrain DN. Objective: The main objective of this exploration was to elucidate the effect of BTE-TF on DN, though the underlying mechanism remains unclear and requires further investigation. Method: The tea leaves were fermented to get black tea extract. Total phenolic content and HPLC were carried out to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This confirmed diabetic nephropathy [ 44 ]. High levels of UCr, SCr, Bun, and GFR indicated the severely impaired glomerular filtration potential in diabetic mice (MC) ( Figure 3 C–F), which was similar to the findings of Sarkar et al [ 11 ] and Mohan et al [ 31 ]. Additionally, images of HE-stained paraffin sections showed various pathological changes, such as glomerular mesangial expansion, glomerular hyaline, glomerular atrophy, and others, in the kidney tissue of diabetic mice (MC) ( Figure 4 C,D).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This confirmed diabetic nephropathy [ 44 ]. High levels of UCr, SCr, Bun, and GFR indicated the severely impaired glomerular filtration potential in diabetic mice (MC) ( Figure 3 C–F), which was similar to the findings of Sarkar et al [ 11 ] and Mohan et al [ 31 ]. Additionally, images of HE-stained paraffin sections showed various pathological changes, such as glomerular mesangial expansion, glomerular hyaline, glomerular atrophy, and others, in the kidney tissue of diabetic mice (MC) ( Figure 4 C,D).…”
Section: Discussionsupporting
confidence: 88%
“…Findings from recent studies have demonstrated that TFs not only protect kidneys through antioxidant, anti-inflammatory, and anticancer pharmacological effects [ 6 , 7 , 8 , 9 ] but also improve T2DM, hypertension, and hyperlipidemia caused by obesity [ 10 ]. Meanwhile, Sarkar et al [ 11 ] showed that black tea extract rich in TFs exhibits a protective role against diabetic nephropathy in rats. However, even though the protective effects of TFs against diabetic nephropathy have been reported, the intrinsic molecular mechanism of action of theaflavins in diabetic nephropathy is not fully clear.…”
Section: Introductionmentioning
confidence: 99%
“…A short-term exposure to oxidants increases the activity of endogenic antioxidants, which suggests activation of defensive mechanisms and adaptive cell response, but under the conditions of long-term oxidative stress, their activity is clearly lowered due to the expulsion of antioxidative metals from active enzyme centers [19,163]. Theaflavin administered to rats with induced diabetes lowered the levels of lipid peroxidation markers as well as other oxidative stress markers, while increasing the activity of antioxidative enzymes and exogenous non-enzymatic antioxidants [119,125,164]. During in vitro digestion of a water extract of matcha tea, polyphenols become more bioavailable and are characterized by higher antioxidative and antidiabetic activity when compared to sencha tea [165].…”
Section: Antioxidative Activitymentioning
confidence: 99%